Transposition and duplication of MADS-domain transcription factor genes in annual and perennial Arabis species modulates flowering - Madrid, Eva; Severing, Edouard; Ansorena, Elisa de; Kiefer, Christiane; Brand, Luise; Martinez-Gallegos, Rafael; Woetzel, Stefan; Kemi, Ulla; Jiao, Wen-Biao; Schneeberger, Korbinian; Coupland, George (Proceedings of the National Academy of Sciences of the United States of America)
The timing of reproduction is an adaptive trait in many organisms. In plants, the timing, duration, and intensity of flowering differ between annual and perennial species. To identify interspecies variation in these traits, we studied introgression lines derived from hybridization of annual and perennial species, Arabis montbretiana and Arabis alpina, respectively. Recombination mapping identified two tandem A. montbretiana genes encoding MADS-domain transcription factors that confer extreme late flowering on A. alpina. These genes are related to the MADS AFFECTING FLOWERING (MAF) cluster of floral repressors of other Brassicaceae species and were named A. montbretiana (Am) MAF-RELATED (MAR) genes. AmMAR1 but not AmMAR2 prevented floral induction at the shoot apex of A. alpina, strongly enhancing the effect of the MAF cluster, and MAR1 is absent from the genomes of all A. alpina accessions analyzed. Exposure of plants to cold (vernalization) represses AmMAR1 transcription and overcomes its inhibition of flowering. Assembly of the tandem arrays of MAR and MAF genes of six A. alpina accessions and three related species using PacBio long-sequence reads demonstrated that the MARs arose within the Arabis genus by interchromosomal transposition of a MAF1-like gene followed by tandem duplication. Time-resolved comparative RNA-sequencing (RNA-seq) suggested that AmMAR1 may be retained in A. montbretiana to enhance the effect of the AmMAF cluster and extend the duration of vernalization required for flowering. Our results demonstrate that MAF genes transposed independently in different Brassicaceae lineages and suggest that they were retained to modulate adaptive flowering responses that differ even among closely related species.
Gesehen am 15.02.2022